Numerical Investigation of the Effect of Velocity on the Central Collision Between Two Water Droplets - Yu, Weidong; Chang Shinan (IET Conference Proceedings, 2018)
Droplet collision is a frequent event in the spray process of icing wind tunnel, the collision outcome can affect the droplet size and velocity distribution in the spray, and thus the performance of the icing wind tunnel. In this paper, the central collision between two equal-sized and unequal-sized water droplets is numerically investigated by using the volume of fluid (VOF) method. The reliability of the procedure is first validated by available experimental data. Then with increasing the relative velocity and keeping the relative velocity constant, the study for the effect of velocity on the central collision between two water droplets is performed. The time evolution of the collision process, the number of satellite droplets formed, the development of flow field and the variation of the kinetic and surface energy are obtained. For unequal-sized droplet collison, the spreading process of one droplet into the other is also presented.